Ceramic Cutting Tools: Development, Characteristics and Prospects - Maulid Purnawan (Balai Besar Keramik, 2018)
Cutting tools in the machinery industry that work at high speeds around 100000-150000 rpm with feed rates above 100 m / min require special specifications namely hardness> 14.5 GPa, toughness> 4 MPa.m1 / 2 for turning inserts,> 8 MPa. m1 / 2 for drill, and> 15 MPa.m1 / 2 for tap and good wear resistance at high working temperatures.The specifications are filled with ceramic material which has a high melting point, high hardness, good chemical stability, high oxidation and corrosion resistance.In general, ceramic cutting tools are grouped into three types, namely alumina-based cutting tools, silicon nitride and cutting tools which are coated with ceramic material with a thickness of 4-15 μm.Commercially, ceramic cutting tools have been applied to the machinery industry in Indonesia, but their needs are still imported because there are no domestic ceramic cutting tools manufacturers. Therefore, the development of the ceramic cutting tool industry in Indonesia has good prospects.Development of the latest ceramic cutting tool products are cutting tools coated with AlTiN which have better thermal resistance and wear time compared to carbide compounds, cermet-based cutting tools capable of working at cutting speeds of 300-500 m / min and whisker reinforced ceramic cutting tools which fabricated in situ or carbon substitution.